1999
DOI: 10.1128/jcm.37.3.742-747.1999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Commercial Kits and Arbitrarily Primed PCR for Identification and Differentiation of Actinobacillus actinomycetemcomitans , Haemophilus aphrophilus , and Haemophilus paraphrophilus

Abstract: The closely related species Actinobacillus actinomycetemcomitans, Haemophilus aphrophilus, and Haemophilus paraphrophilus are common findings in oral microbiota. The aims of this study were to evaluate the applicability of the Rapid NH and API ZYM kits and arbitrarily primed PCR (AP-PCR) in the identification and differentiation of the three species from each other. The material included 62 clinical isolates and three reference strains of A. actinomycetemcomitans representing the 5 serotypes and 18 AP-PCR geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Within the species A. actinomycetemcomitans, all the presently detected four serotypes and four arbitrarily primed‐PCR (AP‐PCR) genotypes are commonly found in the oral cavities of Finnish subjects (11, 12). Among the present H. aphrophilus strains, two of the six AP‐PCR genotypes were similar to and four of six AP‐PCR genotypes were different from those previously observed among oral strains (13). This may be due to the limited data on the AP‐PCR genotyping of oral H. aphrophilus comprising only 11 strains (13).…”
Section: Resultssupporting
confidence: 45%
See 2 more Smart Citations
“…Within the species A. actinomycetemcomitans, all the presently detected four serotypes and four arbitrarily primed‐PCR (AP‐PCR) genotypes are commonly found in the oral cavities of Finnish subjects (11, 12). Among the present H. aphrophilus strains, two of the six AP‐PCR genotypes were similar to and four of six AP‐PCR genotypes were different from those previously observed among oral strains (13). This may be due to the limited data on the AP‐PCR genotyping of oral H. aphrophilus comprising only 11 strains (13).…”
Section: Resultssupporting
confidence: 45%
“…This could be true in laboratories which routinely discard the plates after 2 days of incubation. In addition, inaccuracy of identification kits (13), obliging the primary laboratories to forward the samples to reference laboratories, may delay the correct diagnosis of the patient. In the present study, all strains were identified by a reference laboratory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AP‐PCR genotyping of the A. actinomycetemcomitans isolates was performed as described previously (Saarela et al 1992, Asikainen et al 1995, Doğan et al 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting AP‐PCR products will represent a variety of different‐sized DNA fragments that are visualized by agarose gel electrophoresis. This method has been applied to A. actinomycetemcomitans and P. gingivalis (Dogan et al 1999a).…”
Section: Methods Of Typing Microorganismsmentioning
confidence: 99%